PENENTUAN AKTIVITAS ENZIM LACCASE Rhus vernicifera MENGGUNAKAN GUAIACOL SEBAGAI SUBSTRAT - desriany astina (Jurnal Penelitian Farmasi Indonesia, 2016)
The enzyme laccase (EC.1.10.3.2: oxygen oxidoreductase) is an extracellular enzyme that has a benefit in various industrial fields. This enzyme catalyzes the oxidation of various inorganic and organic compounds such as phenolic compounds, diamine, aromatic amines and ascorbic acid (Mayer and Staples, 2002). Laccase enzyme was first isolated by Yoshida in 1883. He extracted from the Japanese lacquer tree (Rhus vernicifera) (Thurston, 1994; Risdianto, 2008 ; Shraddha dkk., 2011). Objectives of this study is to determine the commercial activity of the enzyme laccase derived from Rhus vernicifera using guaiacol as a substrate. The enzyme activity was measured using a UV-Vis spectrophotometer Thermo Scientific GENESYS 10S at a wavelength of 490 nm using guaiacol as substrate. The results of this study indicate that this enzyme has an activity of 0,0247 ± 0,0002 U/L (at pH 5,5 and a temperature of 40 oC).